Relação entre a cinemática do retropé, tíbia e fêmur em corredores com e sem dor patelofemoral - Luz, Bruna Calazans (2017)
Patellofemoral pain (PFP) is the most common running overuse injury. Excessive rearfoot eversion is commonly considered as a risk factor for patellofemoral pain and the relationship between the ankle-foot complex movement and the lower limb may be involved with this dysfunction. The purpose of this study was to evaluate the relationship between rearfoot eversion with tibia and femur kinematics in frontal and transverse planes during running in individuals with and without PFP. Methods: Fifty-four recreational runners were divided into 2 groups: healthy runners (CG, n = 27) and runners with patellofemoral pain (PFPG, n = 27). Kinematics during running were assessed using a three-dimensional motion analysis. Pearson's correlation coefficients (r) were calculated to establish the relationship of rearfoot eversion with tibial and femur movements (peak and range of motion). Findings: Greater peak rearfoot eversion was associated with greater peak tibial internal rotation and peak femur adduction in the PFPG. Additionally, greater peak rearfoot eversion was associated with greater femur adduction, femur external rotation and tibial adduction range of motion in the PFPG. Interpretation: Strongest associations between the greater rearfoot eversion and the greater peak hip adduction and hip adduction range of motion might be related to the etiology and/or persistence of patellofemoral pain, and indicate that treatment strategies aimed at controlling the movement of the rearfoot could help modify the symptoms.